대·중소 및 중견 기업의 ESG 성과와 재무가치 간의 상관관계 분석 - 박순애; Soonae Park; 신은혜; Eunhae Shin (환경정책, 2021)
최근 금융위원회는 2030년까지 모든 상장기업에 대하여 ESG 전 분야에 대한 공시를 의무화하겠다는 계획을 발표했다. ESG 전담 조직을 꾸릴 수 있는 여유자원을 가진 대기업과 달리 중소·중견 기업들은 급격한 정책 변화로 인하여 단기적으로 손실에 노출될 가능성이 크다. 이에 본 연구에서는 한국기업지배구조원의 ESG 평가 자료를 바탕으로 기업의 규모에 따라 비재무적 ESG 성과를 위한 기업의 노력과 재무상태, 단기 기업가치, 장기 기업가치의 3가지 재무적 지표 간의 관계를 분석하였다. 분석결과, 첫째 ESG 등급과 기업규모별 재무적 성과를 검토한 결과, 집단 간 차이는 중견기업에서만 발견되었으나, 회귀분석 결과는 대기업을 제외한 중소·중견기업 모두 통계적으로 유의한 정의 관계를 보여주었다. 둘째, ESG 성과와 장기 기업가치 간의 관계에 대한 분석결과, 대기업, 중견기업, 중소기업 모두 장기 기업가치와 ESG 등급 간에 통계적으로 유의한 차이가 있는 것으로 조사되었으나, 회귀분석 결과는 중견기업과 대기업에서만 유의한 정의 관계가 있는 것으로 나타났다. 특히 중소기업의 경우 오히려 장기 기업가치가 낮은 집단이 ESG 성과가 높은 역의 관계가 나타나 ESG 관련 규제당국이 주목해야 할 부분이다. 셋째, 기업의 단기가치와 관계에서는 대기업과 중소기업은 유의하지 않았으나 중견기업의 경우 유의한 차이가 있는 것으로 나타났으며 이는 회귀분석에서도 통계적으로 유의한 부의 관계를 보여주고 있다. 전반적으로 ESG 성과와 재무적 지표들 간의 관계는 중견기업에서 가장 확연하고 뚜렷하게 나타났다. 중견기업에서 ESG 성과가 좋은 기업이 재무적 성과와 장기 기업가치도 개선되었지만, 단기 기업가치와는 역의 관계를 보여준 반면, 중소기업과 대기업의 경우 예상과 달리 중견기업만큼 그 관계가 강하게 나타나지는 않았다. 따라서 중소·중견 기업을 대상으로 공시 의무화 등 기업의 ESG 참여확대를 위한 정책이 장기적으로는 기업의 경영성과에 도움이 된다고 할지라도 단기적으로는 기업운영에 타격을 입을 수가 있으므로 정부의 보완책이 필요한 부분이다. The Korean government recently announced a plan to expand the mandatory disclosure of ESG information for all KOSPI-listed companies by 2030. While large corporations with resources can effectively comply with ESG-related regulations, SMEs (small and medium-sized enterprises) may become financially stressed by the rapid policy changes. Using the Korea Corporate Governance Service’s ESG data, this study examines the relationships between ESG performance and three financial indicators: financial performance, short-term corporate value, and long-term corporate value, according to corporate size. It demonstrates that, first, SMEs have a statistically significant positive correlation between ESG performance and financial performance, while large companies do not. Second, companies of all sizes have a statistically significant difference between ESG performance and long-term corporate value. However, in terms of direction, small companies show a inverse relationship of which ESG-related regulators should be prudent. Third, large and small companies do not show a significant relationship between ESG performance and short-term value, while mid-sized companies show a statistically significant negative relationship. Overall, the relationship between ESG performance and financial indicators is most pronounced and evident in mid-sized companies. In mid-sized companies, companies with good ESG performance have better financial performance and better long-term corporate value but show a negative relationship to short-term corporate value. The relationship for large and small companies is not as strong as mid-sized companies. Therefore, although the expansion of such disclosure for SMEs may attract investors for capital raising and eventually help enhance business performance, the government’s supplementary measures are needed. Administrators should be more cautious because the policy changes may hurt business operations in the short term.